Granuloma leproide canino: Estudo de 27 casos - Wurster, Fabiana (2017)
Canine leproid granuloma (CLG) is cutaneous diseases caused by mycobacteria thatcourse with nodular cutaneous or subcutaneous lesion, typically self-limiting, due to Mycobacteriuminfection. It is an unusual dermatological disease, usually reported in tropicalcountries. The objective of the present study is to describe the epidemiological and histopathologicalfindings of CLG. Furthermore, use additional tests for demonstration of Mycobacteriumsp. in the lesion were performed, e.g. Ziehl-Neelsen staining, immunohistochemicaland polymerase chain reaction (PCR) for classification and genetic sequencing of Mycobacteriumspecies. Twenty seven cases of CLG diagnosed between 2005 and 2014 were studied(21 cases by histological examination and six by cytological examination). Boxer dogs werethe breed most affected (33.3%) followed by Dachshund dog breed (11.1%). The diseaseaffected dogs with mainly large size (64%) and short-coated (96%). There was no evidencepredilection for occurrence in any season. The lesions were localized, in most cases, at thepinna (93%), comprise one or multiple nodules, ulcerated or not. None of the cases wasobserved with systemic involvement. Histopathological findings included three patterns ofnodular to diffuse, with inflammatory infiltration granulomatous/pyogranulomatous thatinvolved superficial and deep dermis. Definitive diagnosis was made by the presence of acid--fast bacilli by Ziehl-Neelsen stain, showing wide variation in the number of bacilli in thelesions, not being statistically correlated to the type of injury or the evolution period. Immunohistochemistrywas effective, and in some cases facilitated the identification of bacilli,but in two cases were negative even with marking by Ziehl-Neelsen staining. The immunohistochemistrywas positive in 90% cases, and in some cases facilitated the identification ofbacilli, but in two cases were negative even with marking by Ziehl-Neelsen staining. The PCRtechnique was positive in 44% of cases, demonstrating that Mycobacterium murphy was responsiblefor two cases of GLC and Mycobacterium hodleri by a one case. In other three PCR--positive cases if not got 100% similarity between the sequenced and other Mycobacterium.